Krista Dalton of Ancient Jew Review - Newton, Richard (Bulletin for the study of religion, 2021)
Krista Dalton, assistant professor of religious studies at Kenyon College, joins Bulletin editor Richard Newton to discuss her academic origins and the current trends within religious studies. From her early interests in biblical studies, rabbinics, and Jewish studies to her work as a co-founder of Ancient Jew Review, Dalton answers the questions many scholars—early career and senior faculty alike—find themselves asking. Breaking down academic hierarchy to promote learning at any level is key for Dalton and her pedagogical theory is apparent in all her scholarly efforts.